Pulse processing in optical fibers using the temporal Radon-Wigner transform - Bulus Rossini, Laureano A. (2011)
It is presented the use of the temporal Radon-Wigner transform (RWT), which is the squared modulus of the fractional Fourier transform (FRT) for a varying fractional order p, as a processing tool for pulses with FWHM of ps-tens of ps. For analysis purposes, the complete numerical generation of the RWT with 0 < p < 1 is proposed to select a particular pulse shape related to a determined value of p. To this end, the amplitude and phase of the signal to be processed are obtained using a pulse characterization technique. To synthesize the processed pulse, the selected FRT irradiance is optically produced employing a photonic device that combines phase modulation and dispersive transmission. The practical implementation of this device involves a scaling factor that depends on the modulation and dispersive parameters. It is explored the variation of this factor in order to obtain an enhancement of the particular characteristic sought in the pulse to be synthesized. To illustrate the implementation of the proposed method, numerical simulations of its application to compress signals commonly found in fiber optic transmission systems, are performed. The examples presented consider chirped Gaussian pulses and pulses distorted by group velocity dispersion and self-phase modulation.